Implementation of Collaborative-Based Learning Models in Improving the Quality of Learning Fiqh Lessons - Muhammad Azhari; Herman, Herman; Rahimi, Rahimi; Saputra, Rahmat (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this research is to find out how the steps of implementing a collaborative-based learning model in improving the quality of learning fiqh lessons. This type of research is qualitative library research with a literature review approach, with data collection techniques through documents in the form of books, journals, articles, and other documents. Data analysis by means of data reduction, data presentation, and conclusion drawing. In analyzing the data, the researcher juxtaposes it with several other studies so that the content is more accurate and in-depth to the results of the discussion. The results showed that the steps of implementing a collaborative-based learning model in improving the quality of learning fiqh lessons were carried out through five stages, including: the first stage of developing fiqh subject matter in accordance with learning objectives, the second stage of forming study groups to discuss and analyze the concepts of fiqh material, the third stage using collaborative learning strategies, including: project-based learning, research-based learning and case-based learning, the fourth stage using digital technology as creating an online digital learning platform and collaboration applications to facilitate discussion and cooperation activities, and the fifth stage evaluating student learning outcomes to determine the level of effectiveness of the collaborative learning model. The findings of this research are expected to be able to add insight to educators, and educational practitioners in implementing collaborative learning models in improving the quality of learning fiqh lessons in madrasah/schools.